Water-based polyhydroxy modified amino resin as well as preparation method and application thereof

By using aqueous polyhydroxy modified amino resin in the tire impregnation system, the problem of using harmful substances in the prior art is solved, and a safe, environmentally friendly and simple process preparation of a glue impregnation liquid is achieved, meeting the needs of industrial production.

CN119859232AActive Publication Date: 2025-04-22CHANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510120095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-22
Estimated Expiration
2045-01-25

AI Technical Summary

Technical Problem

The resorcinol and formaldehyde used in the existing tire impregnation system are harmful to the human body and the environment, and the process is complex and cannot meet the needs of industrial production.

Method used

The aqueous polyhydroxy modified amino resin is prepared by reaction of urea, dialdehyde and polyhydroxy compounds to form a non-toxic and environmentally friendly impregnation liquid. The method includes adjusting reaction conditions such as pH, temperature and reaction time, and controlling the viscosity and solid content of the resin.

Benefits of technology

The preparation of a safe, environmentally friendly and simple process is achieved, which can provide a similar bonding effect compared to traditional RFL glue-impregnation systems while reducing harm to the human body and the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258697340000071
    Figure BDA0005258697340000071
  • Figure BDA0005258697340000081
    Figure BDA0005258697340000081
  • Figure BDA0005258697340000091
    Figure BDA0005258697340000091
Patent Text Reader

Abstract

The invention belongs to the technical field of impregnation liquid preparation, and particularly discloses waterborne polyhydroxy modified amino resin as well as a preparation method and application thereof. After urea and dialdehyde are condensed, the water-based polyhydroxy modified amino resin is prepared from the condensed urea and the condensed dialdehyde and a polyhydroxy compound. Under a weak acidic condition, urea and dialdehyde are condensed, then a polyhydroxy compound is added to prepare water-based polyhydroxy modified amino resin with the solid content of 6-15%, and the water-based polyhydroxy modified amino resin, butadiene-vinylpyridine rubber latex and deionized water are prepared into gum dipping liquid with the solid content of 15-20%. The impregnation liquid does not contain substances harmful to human bodies, such as formaldehyde and resorcinol, and is simple in production process, high in production capacity, beneficial to industrial production and relatively good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dipping solution preparation, and specifically discloses a water-based polyhydroxy modified amino resin and a preparation method and application thereof. Background Art

[0002] As one of the important components of automobiles, the importance and safety of tires are self-evident. Tires are mainly composed of rubber and fiber, but the adhesion between the two is not satisfactory. For this reason, a resorcinol-formaldehyde-butylpyrrolidone latex (RFL) dipping system was developed. RFL greatly improves the interaction between rubber and fiber through chemical reactions and hydrogen bonds, and enhances the stability of tires under high load and high speed conditions. However, since the dipping solution contains harmful substances such as resorcinol and formaldehyde, formaldehyde will be released during the production and application process, which will cause harm to the human body.

[0003] In order to replace the resorcinol used in the preparation of RFL, Meng XZ et al. prepared a simple, low-toxic meta-cresol-formaldehyde-butylpyrrolidone latex (CFL) impregnation system by reacting low-toxic meta-cresol with formaldehyde. When the C / F molar ratio was 1 / 2, the temperature was 80°C, the pH was 8, the reaction time was 2h, and the mass ratio of CF resin / butylpyrrolidone latex was 23 / 100, the peeling force and H extraction force of the PET fiber / rubber composite material after CFL impregnation reached 7.3N / piece and 56.8N, respectively. However, formaldehyde will inevitably be released during the preparation process and use, which will cause harm to human body and the environment.

[0004] The use of some environmentally friendly phenolic compounds, such as tea polyphenols, to replace resorcinol has also become a focus of attention. Huang W et al. used tea polyphenols to prepare a new environmentally friendly nylon 66 fiber impregnation system. Tea polyphenols (TP) were first coated on the fiber surface through hydrogen bonding with PA66 fibers, and then a mixture of propylene glycol triglycidyl ether (GTE), 2-ethyl-4-methylimidazole (MZ) and butylpyrrolidone latex (VP) was used for a second coating. The results show that when the MZ / GTE ratio in the impregnation system is 0.2:1, the H extraction force of the nylon 66 fiber / rubber composite material after impregnation reaches 193.1±7.8N. However, one disadvantage of the impregnation system is that it requires a two-step impregnation coating process, which is more complicated than the RFL impregnation system, and 1ml of tea polyphenols reaches 304 yuan, which is not conducive to industrial production. Moreover, the composition of tea polyphenols in different batches varies greatly after two coatings, which makes it difficult to maintain the stability of the product.

[0005] Some researchers replaced RF with amino resins. For example, Shi ZH et al. synthesized a new type of environmentally friendly polyester fiber impregnation adhesive without resorcinol formaldehyde. First, water-soluble glycerol triglycidyl ether (GLTE) and triethyltetramine (TETA) were mixed at a weight ratio of 5:2 at 60°C for 40 minutes. Then, it was mixed and stirred with latex for 2 hours to prepare a glycerol triglycidyl ether-triethyltetramine-butylpyridine latex system (GTL) impregnation solution to replace the resorcinol-formaldehyde-latex (RFL) impregnation system. The results show that the peel strength of the PET-GTL / rubber composite material is 16.5N / mm, which does not reach the peel strength of the PET-RFL / rubber composite material.

[0006] In fact, the above improved methods cannot meet the needs of industrialization and the preparation process is complicated. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems pointed out in the background technology that the raw materials for preparing the RFL dipping system for industrial use are highly toxic, the existing environmentally friendly dipping system has a short storage period, a complex process flow, and cannot meet the actual application requirements. A preparation method and application method of an aqueous polyhydroxy-modified amino resin for preparing an environmentally friendly dipping solution with a simple process and environmentally friendly, non-toxic raw materials are provided.

[0008] To achieve the above object, the preparation method of the water-based polyhydroxy modified amino resin of the present invention comprises the following steps:

[0009] (1) dissolving urea in deionized water; adding an aqueous solution of a dialdehyde compound dropwise, adjusting the pH to 5 to 6, and reacting until the aldehyde group is fully reacted;

[0010] Wherein, the dialdehyde compound is glyoxal, glutaraldehyde or a mixture thereof.

[0011] The reaction temperature is 55 to 85°C, preferably 65 to 75°C.

[0012] The reaction time is 2 to 8 hours, preferably 3 to 5 hours.

[0013] The molar ratio of the dialdehyde compound to urea is 0.5 to 1.2:1, preferably 0.8 to 1.0:1.

[0014] (2) Add a polyhydroxy compound dropwise to the product of step (1) to control the viscosity of the reaction solution to 0.80-3.00 mPa·s; and adjust the pH to 7-8.

[0015] The polyhydroxy compound added dropwise is one of pentaerythritol, polyvinyl alcohol and triethanolamine, or a mixture of several of them.

[0016] The molar ratio of the added polyhydroxy compound to urea is 0.02-0.2:1, and the molar ratio decreases as the hydroxyl group of the polyhydroxy compound increases. The molar amount of polyvinyl alcohol is the molar number converted from the molecular weight of the monomer vinyl alcohol.

[0017] The molar ratio of the polyhydroxy compound added dropwise to urea is preferably 0.05 to 0.15:1.

[0018] The solid content of the water-based polyhydroxy modified amino resin prepared by the above method is 6 to 15%, preferably 6 to 10%.

[0019] The aqueous polyhydroxy modified amino resin prepared by the above method is used to prepare the dipping solution. First, it is prepared according to the weight percentage: 31-37% of 40±5% butylpyrrolidone latex, 36-40% of 6-15% aqueous polyhydroxy modified amino resin, and 23-30% of deionized water; then ammonia water is used to adjust the pH to 9-11.

[0020] The steps of preparing the dipping solution are as follows:

[0021] (1) Take 40±5% butylpyrrolidone latex and add water-based polyhydroxy modified amino resin dropwise; then add deionized water to adjust the ratio.

[0022] (2) Adjust the pH to 9-11 with aqueous ammonia;

[0023] (3) Curing at room temperature for 15 to 20 hours.

[0024] Wherein, the pH in step (2) is preferably 9.5 to 10.5;

[0025] The aging time in step (3) is preferably 16 to 18 hours.

[0026] Beneficial effects: The water-based polyhydroxy modified amino resin used in the dipping system prepared by the present invention is prepared from urea, dialdehyde and polyhydroxy compounds, and the raw materials do not contain formaldehyde and meta-diphenol, which reduces the damage to the human body and the environment; the resin viscosity and solid content can be consistent with the RF resin, which is conducive to the preparation of the dipping system. The preparation process of the water-based polyhydroxy modified amino resin is simple, the cost is low, and the production process is controllable; and the prepared water-based polyhydroxy modified amino resin has many active groups, which is conducive to the connection with fibers and rubber. DETAILED DESCRIPTION

[0027] The present application is exemplified below in conjunction with specific embodiments, but the embodiments are given only as examples and are not considered to be the entire technical solution of the present invention, nor are they intended to limit the overall technical solution of the present invention. Any simple change or replacement of the same or similar technical features shall fall within the scope of protection of the present invention.

[0028] Preparation Example of Waterborne Polyhydroxy Modified Amino Resin:

[0029] Example 1

[0030] 4.03 g (0.067 mol) of urea and 88.10 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 75°C; 5.86 g (0.04 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 75°C for 5 h, 0.96 g (0.0074 mol) of polyvinyl alcohol was added, and the mixture was kept warm for 0.5 h, then cooled to room temperature, the viscosity of the reaction solution was measured to be 1.68 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 6.50%.

[0031] Example 2

[0032] 4.05 g (0.067 mol) of urea and 107.41 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 75°C; 9.66 g (0.067 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 75°C for 5 h, 0.87 g (0.0067 mol) of polyvinyl alcohol was added, the temperature was kept at 75°C for 0.5 h, and then the reaction was cooled to room temperature. The viscosity of the reaction solution was measured to be 1.94 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 6.53%.

[0033] Example 3

[0034] 4.02 g (0.067 mol) of urea and 107.89 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 55° C.; 9.69 g (0.067 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 55° C. for 5 h, 1.33 g (0.0087 mol) of polyvinyl alcohol was added, and the mixture was kept warm for 0.5 h, then cooled to room temperature, the viscosity of the reaction solution was measured to be 1.35 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 6.49%.

[0035] Example 4

[0036] 4.03 g (0.067 mol) of urea and 107.40 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 75°C; 9.68 g (0.067 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 75°C for 7 h, 0.46 g (0.0034 mol) of pentaerythritol was added, and the mixture was kept warm for 0.5 h, then cooled to room temperature, the viscosity of the reaction solution was measured to be 2.32 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 6.52%.

[0037] Example 5

[0038] 4.05 g (0.067 mol) of urea and 100.12 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 85° C.; 11.75 g (0.081 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 85° C. for 2 h, 0.70 g (0.0047 mol) of triethanolamine was added, and the mixture was kept warm for 0.5 h, then cooled to room temperature, the viscosity of the reaction solution was measured to be 1.81 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 7.52%.

[0039] Example 6

[0040] 4.01 g (0.067 mol) of urea and 67.39 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 75°C; 9.67 g (0.067 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 75°C for 5 h, 0.78 g (0.0060 mol) of polyvinyl alcohol was added, the temperature was kept at 0.5 h, and then cooled to room temperature. The viscosity of the reaction solution was measured to be 2.17 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 9.72%.

[0041] Example 7

[0042] 8.04 g (0.134 mol) of urea and 80.50 mL of deionized water were added to a 250 mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 75°C; 19.41 g (0.134 mol) of a 40% glyoxal aqueous solution was added dropwise, and the solution was dripped over 0.5 h; the pH was adjusted to 6 with a 3 mol / L sodium hydroxide solution, the temperature was controlled at 75°C for 5 h, 0.52 g (0.0040 mol) of polyvinyl alcohol was added, the temperature was kept at 0.5 h, and then cooled to room temperature. The viscosity of the reaction solution was measured to be 2.59 mPa·s, and then ammonia water was added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy-modified amino resin was 14.62%.

[0043] Example 8

[0044] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 4.05g (0.067mol) of urea and 135.62mL of deionized water were added in sequence; heating and stirring were turned on, the urea gradually dissolved, the solution became clear, and the reaction temperature was controlled at about 65°C; 10.81g (0.054mol) of 50% glutaraldehyde aqueous solution was added dropwise, and the solution was dripped over 0.5h; the pH was adjusted to 6 with 3mol / L sodium hydroxide solution, and the temperature was controlled at 65°C for 4h. After adding 0.70g (0.0047mol) of triethanolamine and keeping the temperature for 0.5h, it was cooled to room temperature, and the viscosity of the reaction solution was measured to be 1.89mPa·s, and then ammonia water was added to adjust the pH of the solution to 7, and the solid content of the obtained water-based polyhydroxy modified amino resin was 6.28%.

[0045] Example 9

[0046] 4.02g (0.067mol) urea and 142.69mL deionized water were added to a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel. The urea was gradually dissolved and the solution became clear. The reaction temperature was controlled at about 55°C. 16.10g (0.080mol) of 50% glutaraldehyde aqueous solution was added dropwise for 0.5h. The pH was adjusted to 6 with a 3mol / L sodium hydroxide solution and the temperature was controlled at 55°C for 5h. 0.46g (0.0034mol) of pentaerythritol was added and the temperature was kept at 55°C for 0.5h. The reaction was cooled to room temperature. The viscosity of the reaction solution was measured to be 1.75mPa·s. Ammonia water was then added to adjust the pH of the solution to 7. The solid content of the obtained water-based polyhydroxy modified amino resin was 7.41%.

[0047] Comparative Example 1

[0048] In a 250mL four-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, 7.38g (0.067mol) of resorcinol and 158.45mL of deionized water were added in sequence; the solution was stirred under heating until it became clear, and the pH was adjusted to 9 with a 3mol / L sodium hydroxide solution; the reaction temperature was gradually raised to 25°C, and 10.88g (0.134mol) of a 37% formaldehyde aqueous solution was added dropwise, and the dripping was completed in 0.5h, and the temperature was controlled at 25°C for 6h. The obtained resorcinol-formaldehyde (RF) resin had a solid content of 6.45% and a viscosity of 1.42mPa·s.

[0049] The results of the examples of modified amino resins and RF with different solid contents are shown in Table 1.

[0050] Table 1

[0051]

[0052] Example of preparing environmentally friendly dipping solution:

[0053] Example 10

[0054] Weigh 24.70g, 24.72g, 24.69g, 24.73g, 24.70g, 24.68g, 24.71g, 24.69g, 24.72g, and 24.68g of 40% butylpyrrolidone latex into 10 100mL beakers and mark them as dipping solutions 1 to 10. 17.71g, 17.69g, 17.75g, 17.72g, 17.70g, 17.70g, 17.71g, 17.70g, 17.69g, 17.71g deionized water were added to dipping solutions 1 to 10 respectively, and then 26.60g, 26.63g, 26.62g, 26.60g, 26.62g, 26.61g, 26.61g, 26.60g, 26.62g, 26.60g of the water-based polyhydroxy modified amino resin prepared in Examples 1 to 9 and 26.60g, 26.63g, 26.62g, 26.60g, 26.62g, 26.61g, 26.61g, 26.60g, 26.62g, 26.60g of the RF resin prepared in the comparative example were weighed and added dropwise to dipping solutions 1 to 10; pH was adjusted to 10 with ammonia water. Ripen at room temperature for 16 hours. The prepared dipping solutions were observed, and the results are shown in Table 2 below.

[0055] Table 2

[0056]

[0057] H extraction force test example:

[0058] Embodiment 11

[0059] Dipping and drying: Use the above dipping solutions 1-10 in sequence to dipping nylon fibers in a continuous method, and then dry. The dipping solution temperature is controlled at 25±5℃, the fiber stays in the dipping solution for 0.5 seconds, and then is dried in an oven at a drying temperature of 130±5℃ for 1min; 135±5℃, curing for 50min. The impregnated fiber is then stored away from light for subsequent use.

[0060] According to the standard GB / T2942-2009 method, the above-mentioned dipped fibers were used to prepare samples. A 10mm×10mm×10mm rubber strip was used, the vulcanization temperature was 135±5℃, the vulcanization pressure was 3MPa, the vulcanization time was 50min, and the fibers were cooled to room temperature. Eight samples were made for each fiber.

[0061] The H extraction force of the composite material was tested using a universal electronic tensile testing machine in accordance with GB / T2942-2009. During the test, the cord segment was kept vertical, and the tensile test was performed at a speed of 100±10mm / min. The maximum tensile force during the process of the cord being pulled out of the rubber was recorded, and the average value was taken for each group of 8 samples.

[0062] The test results are shown in Table 3:

[0063] Table 3

[0064]

[0065] H extraction force test, the test requirement in the industrial production process is not less than 120N. The results show that the H extraction force of the dipping solution of the present invention meets the industrial requirements, indicating that the nylon fiber and rubber have a good bonding effect, reaching the bonding level of traditional RFL, and can replace the RFL dipping solution. The water-based polyhydroxy modified amino resin used in the present invention does not contain formaldehyde and resorcinol, and has a good application prospect.

Claims

1. A method for preparing a water-based polyhydroxy modified amino resin, characterized in that: The preparation method steps are as follows: (1) Dissolve urea in deionized water, then add an aqueous solution of a dialdehyde compound and adjust the pH to 5-6 to allow the aldehyde group to fully react; (2) Adding a polyhydroxy compound to the product of step (1) to control the viscosity of the reaction solution to 0.80-3.00 mPa·s; and adjusting the pH to 7-8.

2. The method for preparing the water-based polyhydroxy modified amino resin according to claim 1, characterized in that: In step (1), the dialdehyde compound is glyoxal, glutaraldehyde or a mixture thereof.

3. The method for preparing the water-based polyhydroxy modified amino resin according to claim 1, characterized in that: In step (1), the molar ratio of the dialdehyde compound to urea is 0.5-1.2:

1.

4. The method for preparing the water-based polyhydroxy modified amino resin according to claim 1, characterized in that: In step (1), the reaction temperature is 55 to 85° C. and the reaction time is 2 to 8 hours.

5. The method for preparing the water-based polyhydroxy modified amino resin according to claim 1, characterized in that: In step (2), the added polyhydroxy compound is one or a mixture of pentaerythritol, polyvinyl alcohol and triethanolamine.

6. The method for preparing the water-based polyhydroxy modified amino resin according to claim 1, characterized in that: In step (2), the molar ratio of the added polyhydroxy compound to urea is 0.02-0.2:

1.

7. A water-based polyhydroxy-modified amino resin prepared according to the method according to any one of claims 1 to 6, characterized in that: The solid content of the water-based polyhydroxy modified amino resin is 6-15%.

8. An application of a water-based polyhydroxy-modified amino resin prepared by the method according to any one of claims 1 to 6, characterized in that: The water-based polyhydroxy modified amino resin is used for preparing an environmentally friendly dipping solution.

9. The use of the water-based polyhydroxy modified amino resin according to claim 8, characterized in that: The composition of the environmentally friendly dipping solution by weight percentage is: 31-37% of 40±5% butylpyrrolidone latex, 36-40% of 6-15% water-based polyhydroxy modified amino resin, and 23-30% of deionized water.

10. The use of the waterborne polyhydroxy modified amino resin according to claim 8, characterized in that: The preparation method of the environmentally friendly dipping solution comprises the following steps: (1) Take 40±5% butylpyrrolidone latex, add water-based polyhydroxy modified amino resin dropwise, and then add deionized water to adjust the ratio; (2) Adjust the pH to 9-11 with aqueous ammonia and mature at room temperature for 15-20 hours.

Citation Information

Patent Citations

  • Phenol modified urea formaldehyde fiber preparation method

    CN110359118A

  • Method for preparing melamine modified urea-formaldehyde fiber by repeated addition

    CN110373737A

  • Impregnation system for fiber surface treatment and fiber and preparation method thereof

    CN118910890A

  • Preparation method of environment-friendly modified glyoxal water repellent agent

    CN119194899A

  • Preparation of aqueous nonwoven binders of low formaldehyde emission on curing based on urea, formaldehyde and glyoxal

    US5017641A